Visual evoked potentials in 4-year old prematurely born children - Leśniak, Anna; Kubatko-Zielińska, Anna; Klimek, Małgorzata; Pociej-Marciak, Weronika; Romanowska-Dixon, Bożena; Kwinta, Przemko (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Objective : To determine a relationship between the severity of retinopathy of prematurity and visual evoked potential findings in 4-year old prematurely born children with very low birth body weight (<= 1500 g). Material and methods : 71 children with the mean birth weight of 1083 g were qualified for the study. The children were divided into three groups based on the medical history: 1. – children without retinopathy of prematurity (‘without retinopathy’) (n = 28), who were the control group in our study, 2. – children with retinopathy of prematurity, with no indications for laser coagulation (“retinopathy without treatment”) (n = 17), 3. – children with retinopathy of prematurity treated with laser coagulation (“retinopathy + lasers”) (n = 26). Visual evoked potential testing using a Tomey EP-1000 device was performed in all participants. The latency time and the amplitude of the P100 wave were calculated. Results : 14 children with retinopathy of prematurity treated with laser coagulation (54%), 4 children from the group with retinopathy of prematurity that did not require laser coagulation (24%), and 7 children without retinopathy (25%) presented with abnormal visual evoked potential results (p = 0.044). We found statistically significant differences both in the latency time (101 vs. 94.4 vs. 92.4 ms in the groups, respectively; p <0.001) and the P100 wave amplitude (7.1 vs. 11.7 vs. 11.3 mV in the groups, respectively; p <0.001) between the analyzed groups. However, multivariate analysis pointed to the severity of child immaturity rather than the severity of retinopathy of prematurity as an independent variable affecting the visual evoked potential results. Conclusions : The obtained results may indicate disturbances of visual pathway conduction in preterm infants with retinopathy of prematurity treated with laser coagulation. It appears, however, that this disruption is related to the severity of child immaturity with the severity of retinopathy of prematurity being only an indicator of this immaturity. Further studies in larger children cohorts are necessary.